CFD simulations of the gyroscopic precession of a flying disc - Lin, XunJian (Nanyang Technological University, 2020)
This paper analyses the feasibility of designing an Unmanned Aerial Vehicle using the flight properties of a flying disc by simulating the gyroscopic precession of a flying disc in Computational Fluid Dynamics (CFD). By capturing the precession in CFD, one can better understand the stability and control of the flying disc in flight. In this paper, three cases of CFD simulations are conducted. The first two cases are done in two-dimensional domain to study the motion of the flying disc in horizontal and vertical plane independently. Data of the two motions are then simulated in a third case with three-dimensional domain, transient time to study the precession and dynamics of a flying disc.